Pengaruh Sistem Pengukuran Kinerja Strategis, Job Relevant Information, Dan Kejelasan Peran Terhadap Kinerja Manajerial Perguruan Tinggi Swasta Di Bandar Lampung - tarmizi tarmizi; erna listyaningsih; iing lukman (Universitas Malahayati, 2023)
Higher education is one of the educational institutions that are the main means in educating the nation. At this time many universities are established, managed, and developed by the government (state) or private. The main role of universities is to explore by conducting research and transmit knowledge by means of education. Managerial performance is a result of managerial activities that begin with planning, implementing, monitoring business, accountability reports, coaching, and monitoring. Managerial performance can be used to assess the processes and activities of managers in carrying out management functions which are calculated using indicators of planning, investigating, coordinating, evaluating, representing, negotiating, staffing, and supervising.The research design used in this research is explanatory research with a quantitative approach presented with numbers and analysis using statistics. Conducted from December 2021 to July 2022 on 7 private universities in Bandar Lampung where data collection using a questionnaire was then analyzed and presented in the form of a characteristic distribution table.From the results of research conducted by the author that the Strategic Performance Measurement System has a positive influence (O = 0.353) with the performance construct. the value of t – statistic in this construct relationship is 2.103 > 1.96, and the value of p – value is 0.031 < 0.05. Job Relevant Information has a positive effect (O = 0.338) with the performance construct. the value of t – statistic in this construct relationship is 2.072 > 1.96, and the value of p – value is 0.027 < 0.05. Role Clarity has a positive effect (O = 0.335) with the performance construct. the value of t – statistic in this construct relationship is 2.035 > 1.96, and the value of p – value is 0.025 < 0.05.Thus, it can be concluded that the influence of the strategic performance measurement system, job relevant information, and role clarity simultaneously have a significant effect on managerial performance. This shows that each variable is in accordance with what is expected so that managerial performance increases.